Tuber shii sp. nov., a sister species of T. jinshajiangense from China in Puberulum group - Wang, Yanwei; Li, Xuedong; Fan, Li (Phytotaxa, 2016)
A new white truffle species Tuber shii is described and illustrated from China. Both the ML trees generated from ITS and the combined sequences of ITS and nrLSU revealed that T. shii is a distinct species and sister to T. jinshajiangense in phylogeny. Morphologically, the new species can be distinguished from T. jinshajiangense by its ascospore shape dominated with globose spores but often with the presence of subglobose ones. The pattern of relationship between T. shii and T. jinshajiangense is the same as that of European species T. sphaerospermum and T. oligospermum in morphology and phylogeny.